CLOSE ANALYSIS: AN ACTIVITY FOR USING TRANSLATION IN TEACHING WRITING FOR STUDENTS OF ENGLISH AT UNIVERSITY LEVEL - Ramadan Ahmad Shalbag (Abhat Journal, 2018)
The teachers of English language (EL) and students encounter certain difficulties in teaching and learning writing. Zheng 1999 states that acquiring the writing skill seems to be more laborious and demanding than acquiring the other three skills. Nunan (1999:271) considers writing an enormous challenge to produce a "coherent, fluent, extended piece of writing” in one’s second language. Thus, teachers of writing started thinking of combining more than one approach in order to suit all writing tasks and prepare the students for the writing that they have to do after they graduate. The collaboration of adopting more than one approach is one of the changes that happened in English language teaching (ELT). One of the greatest changes was the shift in English language teaching, from a teacher-centered, to a learner- centered approach.